Problems of Investigation of Crimes Committed Against Humanity - Valentukevičius, Rimvydas (Genocidas ir rezistencija, 2025)
From the point of view of international law, supremacy of justice, and the morality of Lithuanians and other nations living in Lithuania and suffering two occupations for more than fifty years, the adoption of such a law was a very necessary and right step. This law gave Lithuania the opportunity to evaluate from a legal point of view that period of its history during which it sustained the brutal, intolerant, and dehumanising ideology of two totalitarian systems – the Nazis and the Soviets. Obviously, Lithuania could not have had such an opportunity during the five decades of occupation.
Keywords: law inforsement institutions; crimes against humanity; international law; Holocaust; Lithuanian law